2007
DOI: 10.1097/mlg.0b013e31805c9a28
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein B Detection and Gene Expression in Chronic Rhinosinusitis

Abstract: This is the first study to detect and characterize SP-B in human sinus mucosa. Furthermore, SP-B is significantly up-regulated in CF CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…In relation to the nasal upper airways, a few studies found expression and localization of SP-A, -B and -D in human nasal epithelium [4,17,18], and, very recently, Schicht et al [12] have confirmed and extended these studies by finding that SP-C was also associated with nasal epithelium. All 4 proteins show more or less the same pattern of localization with prominent immunoreactivity associated with submucosal glands, being more specific within the serous acini but less so within the mucous acini.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In relation to the nasal upper airways, a few studies found expression and localization of SP-A, -B and -D in human nasal epithelium [4,17,18], and, very recently, Schicht et al [12] have confirmed and extended these studies by finding that SP-C was also associated with nasal epithelium. All 4 proteins show more or less the same pattern of localization with prominent immunoreactivity associated with submucosal glands, being more specific within the serous acini but less so within the mucous acini.…”
Section: Discussionsupporting
confidence: 55%
“…Less prominent immunoreactivity was also observed with ciliated cells of the surface nasal epithelium but not with goblet cells. By using RT-PCR, it has also been shown that the synthesis of SP-A, -B, -C and -D occurs locally [4,12,17,33,34]. Although all these publications confirm the presence and production of SP-A, -B, -C and -D in nasal tissue, previously published studies did not focus on the detection of SPs in nasal lavage and mucus.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Indeed, early studies using liposomes, which consist of phospholipids that make up 75% of the nasal surfactant layer, have been found to be comparable to cromoglycolate therapy in the treatment of patients with AR (87). In patients with chronic rhinosinusitis associated with cystic fibrosis, expression of SP-A, SP-B, and SP-D is also increased (88,89).…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…Other innate defense proteins such as surfactant protein (SP) A, SP-B, and SP-D are also upregulated in CF. [31][32][33][34] Other molecular differences between CF and non CF polyps include a significantly higher level of lipoxin A 4 and slightly elevated cyclooxygenase 2 in CF polyps. 35 Onset of bacterial infection and colonization in CF CRS may instigate inflammatory pathways with Toll-like receptors recognizing pathogen-associated molecular patterns with production of these antimicrobial peptides.…”
Section: Pathophysiology Of Crsmentioning
confidence: 99%